Prolegomena for an artistic historiography of Cusco in the rectory of Albert Giesecke of the San Antonio Abad University (1910-1923) - Caparó Aragón, Marco Antonio (2021)
This article raises the idea that the artistic historiography of Cusco (1918-1925) is based on the analysis of Indo-mestizo ideological contents that sought to unite national history through artistic objects. The main objective of this research is to demonstrate that the North American educational policies and curricula in Albert Giesecke's rectory had an influence on Peruvian art studies. The analysis approach used is artistic historiography, in this sense the University Magazine, documents and critical bibliography of Luis Eduardo Valcárcel and José Uriel García were reviewed. Whose axis of inquiry will demonstrate its emergence with the qualification of the chair of History of Peruvian art (1917). As a result, when writing the texts, it was verified that their existence corresponds to protect the Castizo art of the Hispanic, correlated in works by Indo-mestizo artists. The research allows us to conclude that artistic historiography is an expression of the provincial intellectual to rewrite the national identity.